THE COMPLEMENTARY USE OF SOFT SYSTEM METHODOLOGY IN DEVELOPING MSMEs TAX POLICY: CASE STUDY MSMEs IN CIREBON - Syafrani, Dewi; Kasim, Elsie; Arianty, Fitria; Marsdenia, Marsdenia (UI Scholars Hub, 2025)
This research analyze the use of the Soft System Methodology (SSM) method in designing tax policies for Micro, Small and Medium Enterprises (MSMEs). Integrating the SSM approach with tax policy analysis, this research aims to investigate the complex dynamics that influence the development of MSMEs. By considering diverse stakeholder perspectives, this research identifies the needs, interests, and constraints involved in formulating effective tax policies for the MSME sector. The result is that increasing MSME tax compliance requires targeted education to improve awareness and understanding of tax obligations. Simplifying tax administration and balancing sanctions with supportive measures can encourage compliance without pushing MSMEs further into informality. Effective policies should combine fair enforcement with incentives and opportunities for correction to foster a compliant and growth-oriented environment for MSMEs.